Effect of hydrolysis products and Mg2+, Mn2+ and Ca2+ ions on whey lactose hydrolysis and β-galactosidase stability - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (WILEY-BLACKWELL, 2008)
BACKGROUND: Enzyme inhibition is one of the constraints of reactions catalysed by enzymes, and information is required on the inhibition mechanisms that affect the process yield. Therefore the aim of the present study was to investigate the effect of hydrolysis products and ions on the hydrolysis of lactose recovered from whey and enzyme inactivation during the reaction. The experiments were carried out in 250 mL of 25 mmol L-1 phosphate buffer solution using beta-galactosidase from Kluyveromyces marxianus lactis in a batch reactor system. RESULTS: The degree of lactose hydrolysis (%) and the residual enzyme activity (%) in the presence and absence of lactose over time were investigated versus hydrolysate amount, glucose and galactose concentrations and Mg2+, Mn2+ and Ca2+ ion concentrations. The hydrolysis degree decreased with the addition of all hydrolysis products, as enzyme inhibition occurred. The residual enzyme activity increased with the addition of hydrolysate and glucose but decreased with the addition of galactose. It was observed that Mn2+ and Mg2+ ions activated the enzyme. It was also found that the hydrolysis degree was not affected by the addition of Mn2+ ions. On the other hand, the hydrolysis degree decreased with the addition of Ca2+ ions, as the enzyme was inactivated. CONCLUSION: Evaluation of the experimental data showed that both beta-galactosidase activity and lactose hydrolysis were affected by the addition of hydrolysis products and ions. Moreover, mathematical models proposed to predict the residual lactose concentration and residual enzyme activity were confirmed by the experimental results. (c) 2008 Society of Chemical Industry.
Keywords: whey lactose hydrolysis; beta-galactosidase; hydrolysate; glucose; galactose; magnesium; manganese; calcium; modelling; KLUYVEROMYCES-FRAGILIS; STARCH HYDROLYSIS; ESCHERICHIA-COLI; KINETIC-MODEL; INACTIVATION; INHIBITION; BIOREACTOR; SUPPORTS; PERMEATE; REACTOR; Biotechnology & Applied Microbiology; Chemistry; Engineering